Role of the Gastrointestinal Tract Microbiome in the Pathophysiology of Diabetes Mellitus - Muhammad U. Sohail; Asmaa Althani; Haseeb Anwar; Roberto Rizzi; Hany E. Marei (Journal of Diabetes Research)
The incidence of diabetes mellitus is rapidly increasing throughout the world. Although the exact cause of the disease is not fully clear, perhaps, genetics, ethnic origin, obesity, age, and lifestyle are considered as few of many contributory factors for the disease pathogenesis. In recent years, the disease progression is particularly linked with functional and taxonomic alterations in the gastrointestinal tract microbiome. A change in microbial diversity, referred as microbial dysbiosis, alters the gut fermentation profile and intestinal wall integrity and causes metabolic endotoxemia, low-grade inflammation, autoimmunity, and other affiliated metabolic disorders. This article aims to summarize the role of the gut microbiome in the pathogenesis of diabetes. Additionally, we summarize gut microbial dysbiosis in preclinical and clinical diabetes cases reported in literature in the recent years.